Tantangan Hukum dalam Penyelesaian Sengketa E-commerce: Pendekatan Arbitrase dan Litigasi - Kurniawan, Itok Dwi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this research is to analyze Legal Challenges in E-commerce Dispute Resolution: Arbitration and Litigation Approaches. This type of research is a literature review. Data collection with documentation. Data analysis with SLR. Research results Legal challenges in resolving e-commerce disputes involve regulatory complexity which is growing rapidly amidst the dynamics of online transactions. Arbitration and litigation approaches are the two main options that parties involved in e-commerce disputes must consider. Arbitration offers speed and confidentiality, while litigation provides a more structured process and public disclosure of information. However, the biggest challenge remains adapting the existing legal system to the dynamics of changing technology and the ever-growing e-commerce business.